Determining Efficacy of Intracanal Cryotherapy on Post Endodontic Pain in Irreversible Pulpitis: Cryotherapy on Post Endodontic Pain - Bashir, Anam Fayyaz; Jatala, Ussamah Waheed; Ahmad, Moeen ud din; Khan, Muhammad Talha; Khan, Saima Razzaq; Butt, Aisha Arshad (Pakistan Journal of Health Sciences, 2024)
Endodontic cryotherapy is a procedure that reduces pain and inflammation by applying cold to tissues, aiming to decrease post-endodontic pain. Objectives: To compare the effectiveness of cryo-treated endodontic irrigant in reducing post-endodontic pain in mandibular molars with irreversible pulpitis. Methods: This comparative analytical study was conducted from December 2023 to February 2024 in the Department of Operative Dentistry at Lahore Medical and Dental College. It included patients of both genders, aged 18 to 60, with symptomatic irreversible pulpitis in mandibular molars and pre-endodontic pain of VAS 7-10 for 10 days or less. Patients were divided into two groups: Group A (normal saline) and Group B (cryotherapy). Patients were instructed on using the Visual Analogue Scale (VAS) to assess pain. Group B received final irrigation with 20 ml normal saline at 2.5°C for 5 minutes, while Group A received 20 ml normal saline at room temperature. Pain scores were recorded preoperatively and at 24 and 48 hours’ post-treatment via telephone interviews. Data were analyzed using SPSS version 25 and a repeated measures ANOVA test assessed VAS scores across time points. A p-value <0.05 was considered significant. Results: 45 (46%) were male and 53 (54%) were female patients, with mean age of patients being 35.71 ± 10.71years. At 24 hours postoperatively, the mean VAS score was 1.51 ± 1.2 for the normal saline group and 0.98 ± 0.9 for the cryo-treated saline group. By 48 hours postoperatively, the mean VAS score further decreased to 0.27 ± 0.5 for the normal saline group and 0.12 ± 0.4 for the cryo-treated saline group. The mean differences in VAS scores at 24 hours showed significant difference in mean pain score (P-value<0.05) but at 48 hours between the two groups showed no significant difference (p = 0.104). Conclusions: Both saline groups significantly decreased pain, the type of saline, normal or cryo-treated, did not significantly impact overall pain scores differently between the groups.